L’utilisation de la cartographie des valeurs sociales et culturelles comme outil dans l’adaptation aux changements climatiques : exemple d’un projet pilote à l’Île-du-Prince-Édouard (Canada) - Irene Novaczek; Josh MacFadyen; Darren Bardati (VertigO)
Planning, adaptive action and emergency preparedness can reduce or mitigate losses and associated distress resulting from negative impacts of climate change on small islands. However, adaptation plans and strategies are typically developed using only scientific and economic data. These need to be augmented by data that reflect the social and cultural concerns of citizens. Social and cultural values mapping uses Geographic Information System (GIS) to display and analyze social and cultural values that are attached to geographic space. This method brings various knowledge fields together and creates the potential to compare and juxtapose normally invisible human relationships with scientific data on the predicted impacts of climate change. These maps then become tools to assist local governments in planning and prioritizing effective adaptation strategies. In addition, the process of collective map building reassures people that their knowledge and values are respected. This helps develop trust and collaboration in governance which are essential for effective community-level climate change adaptation. Small island governments and community groups are the vanguard of climate change adaptation because small islands are among the most vulnerable places on the planet to the effects of climate change. These jurisdictions will need tools that allow them to improve their resilience, adaptation mechanisms, and ability to speak to international governing bodies. In this paper we report on a pilot study of social and cultural values mapping performed on Prince Edward Island in January - March 2010. We conclude that this methodology has potential as a tool to support decision-making for climate change adaptation, and it can be implemented and modified as required by a variety of stakeholders.